PENGARUH PENGGUNAAN GADGET TERHADAP PENURUNAN KETAJAMAN PENGLIHATAN PADA REMAJA TAHUN 2020 - Qonita Qonita; Zahrah Maulidia Septimar (Nusantara Hasana Berdikari, 2021)
Based on a survey that has been done the increase in children who have used glasses has reached 10%, especially students in the City of South Tangerang. Last year the children who used glasses were caused by the factor of too often using smartphones reaching 24% but now it has reached 10%. Visual acuity disorders in school-age children are important health problems. Early detection and publication of the prevalence and factors associated with visual impairment in primary school students in Indonesia is still very rarely done. Methods: Researchers used data bases such as Google Scholar, Pubmed, and Pro-quest to search for articles by authors conducting searches in Indonesian and English with the keywords